BS 669-1. Flexible hoses, end fittings and sockets for gas burning appliances. Part 1. Strip-wound metallic flexible hoses, covers, end fittings and sockets for domestic appliances burning 1st, 2nd and 3rd family gases. Specification (26th August 2021) - British Standards Institution,
No abstract available